Biochemical potential of four widely consumed African leafy vegetables - Josefa Rangel; Ângela Liberal; Tiane C. Finimundy; Tânia S.P. Pires; Maria M. Romeiras; Ângela Fernandes; Lillian Barros (Food Research International, 2026)

Er and Er/Yb doped TiO2 solar-light-active photocatalysts for minocycline removal from water and wastewaters: Effect of synthesis and immobilization into MICROSCAFS® - Sofia Moreira Fernandes; Beatriz Trindade Barrocas; Ana Maria Ferraria; Luís F. Santos; M. Conceição Oliveira; Markus Niederberger; Ana C. Marques (Chemosphere, 2026)

Anaerobic metabolic responses of sludge and mine wastewater-derived consortia to winery wastewater-related compounds - Ana Baía; Alonso I. Arroyo-Escoto; Nuno Ramos; César Afonso; Gaetano R. Pesce; Maria C. Fernandes; Annabel Fernandes (World Journal of Microbiology and Biotechnology, 2026)
Winery wastewater contains readily biodegradable organic matter, but some of its components can inhibit anaerobic microbial activity. This study compares two enriched microbial consortia, derived from anaerobic digester sludge (ADS) and mining-process wastewater (MPW), exposed to alcohols, carboxylic acids, and phenolics. Assays were conducted in acetate–fumarate-based media containing low or high concentrations of each compound class and a combined condition containing the compounds at their highest levels. Growth, fumarate consumption, succinate production, acetate turnover, and compound consumption were monitored. Full-length 16 S rRNA gene sequencing showed that ADS was dominated by Proteus (56.9%) and Escherichia (28.6%). MPW showed a more even profile dominated by Proteus (35.8%), Wolinella (32.9%), and Escherichia (23.0%). Under control conditions, MPW showed higher growth (0.284 vs. 0.181 h −1 ) and succinate production rates (0.171 vs. 0.106 g L −1 h −1 ) than ADS. Alcohols caused little change in fumarate consumption, but high carboxylic acid concentrations reduced fumarate consumption rates to 0.115 and 0.162 g L −1 h −1 in ADS and MPW, respectively. Phenolics reduced the ADS succinate production rate to 0.059 g L −1 h −1 , while MPW remained near its control value (0.169 vs. 0.171 g L −1 h −1 ). Under combined exposure, ADS maintained fumarate consumption and increased succinate production from 0.106 to 0.157 g L −1 h −1 , but MPW decreased from 0.125 to 0.092 g L −1 h −1 . Both bacterial composition and the chemical conditions of exposure influenced anaerobic resilience. The combined use of taxonomic and metabolic indicators may therefore improve the selection of consortia for the biodegradation and valorization of complex agro-industrial wastewaters, including their integration into bioelectrochemical platforms.

Association between COVID-19 infection, elevated C-reactive protein, and neuropsychiatric symptoms in individuals with metabolic and cardiovascular comorbidities - Gabriel S. Mondo; Lucas C. Pedro; Camila O. Arent; Larissa C. Pereira; Jéssica L. Fernandes; Amanda L. Maciel; Luciane B. Ceretta; Zuleide Maria Ignácio; Gislaine Zilli Réus (Metabolic Brain Disease, 2026)

Corrigendum to “Co-occurrence of microplastics and endocrine-disrupting chemicals in subantarctic seabirds” [J. Hazd. Mater. 509 (2026) 142018] - Joana Fragão; Clara Manno; Richard A. Phillips; Sara C. Cunha; José O. Fernandes; Luís A.E. Batista de Carvalho; Maria Paula M. Marques; José C. Xavier; Filipa Bessa (Journal of Hazardous Materials, 2026)

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Collapse and recovery of the foraminifera during Oceanic Anoxic Event 1b of the Araripe Basin, in Central Gondwana - Anne C.M. Brandão; Rilda C. Araripe; Marlone H.H. Bom; Bruno Fernandes; Maria Coutinho; Alcides N. Sial; Alcina M.S. Franca (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Influence of raw material on the physical-chemical profile of cachaça: effects of variety and sugarcane cutting conditions - Maria Augusta L. S. M. Marques; Maria G. Cardoso; Wilder D. Santiago; Guilherme V. Pimentel; Tharyn Reichel; Antonia Isadora Fernandes; Sara C. S. Silva; Maria Luisa Teixeira; Danubia Ap. C. S. Rezende; David L. Nelson (Food Additives & Contaminants: Part A, 2026)

Co-occurrence of microplastics and endocrine-disrupting chemicals in subantarctic seabirds - Joana Fragão; Clara Manno; Richard A. Phillips; Sara C. Cunha; José O. Fernandes; Luís A.E. Batista de Carvalho; Maria Paula M. Marques; José C. Xavier; Filipa Bessa (Journal of Hazardous Materials, 2026)

Sustainable Location of Reverse Vending Machines - Carlos Gomes da Silva; Maria Eduarda Fernandes; João Maurício C. (Circular Economy and Sustainability, 2026)
Reverse Vending Machines (RVMs) may play a fundamental role in a circular economy, ensuring materials circulate and maintain their greatest utility and value for as long as possible. Location is key to their success and aligning it with regional sustainable development adds complexity to the decision. In this paper we link sustainability with the location of RVMs to reveal, through mathematical models, the inherent trade-offs involved in simultaneously managing the three pillars of sustainability—social, economic, and environmental—when locating RVMs. Spatial interaction behaviours are employed to represent the demand for RVMs, with multiple allocation incorporated into the proposed models. Instead of relying on the common assumption of known and constant demand, we develop a demand function that accounts for both the attractiveness of RVMs and their distances to users. This approach provides a more accurate representation of effective demand patterns, thereby adding a novel contribution to literature. Additionally, real-world data from specific territory is used to illustrate the policy, managerial and operational challenges involved in determining the location of RVMs. The results obtained pinpoint the compromising locations for RVMs aiming the three pillars of sustainability, delivering to the decision makers the balance between them, as well as the impacts of the underlying political options on the location decision. Finally, a sensitivity analysis of the parameters used is performed to assess the robustness of the solutions found.

Quantifying leaf herbivory: A guide to methodological trade‐offs and best practices - Tatiana Cornelissen; Gisele M. Mendes; Fernando A. O. Silveira; Wesley Dáttilo; Roger Guevara; Ramiro Aguilar; Maria Gabriela Boaventura; Ricardo Campos; Ek del Val; Guilherme Ramos Demetrio; Marcilio Fagundes; Rafael de Paiva Farias; et al. (Ecology, 2026)
Leaf herbivory is a ubiquitous ecological interaction that varies significantly in intensity across species, habitats, and biogeographic regions. Although quantification of leaf damage is crucial for understanding many ecological processes, the accuracy and precision of various damage estimation methods used by researchers, including visual estimation, digital image analysis, and artificial intelligence, have not been evaluated and compared. We use a phylogenetically diverse group of tropical plants to compare the accuracy and precision of damage estimation methods and use the results to provide a guide to herbivory estimation that balances the advantages and disadvantages of each method. We found that visual estimation tended to overestimate herbivory levels compared to digital methods but was 15 times faster and improved in accuracy and speed with training. Conversely, deep‐learning algorithms underestimated herbivory relative to image analysis with ImageJ when it was on the margin, but showed similar accuracy for damage inside of leaf margins. Our results indicate that while visual methods allow for rapid assessment of large sample sizes and are suitable for detecting broad patterns of damage, image analysis is crucial for accurate and precise quantification. The disadvantages of each method, however, can be minimized through proper training and efficient use of each tool, and we therefore provide a guide of practical approaches to herbivory estimation.

Why marine gammarids belong to the future portfolio of aquafeed ingredients - Ricardo Calado; Marta Carvalho; Luísa Marques; Daniela P. Rodrigues; João P. Sousa; Felisa Rey; Maria Rosário Domingues; Joana Filipa Fernandes; Ruben X. G. Silva; Diana Madeira; Arne M. Malzahn; Óscar Monroig; et al. (Frontiers in Marine Science, 2025)
The sustainable supply of n-3 long-chain polyunsaturated fatty acids ( n -3 LC-PUFA) remains a major challenge for global aquaculture. Although plant oils, microalgae, genetically modified crops, insects, krill, and fish by-products have been explored as alternative sources, none currently provides a stand-alone solution for meeting the growing demand of n -3 LC-PUFA in aquafeeds’ production. Here, we present marine gammarids as a potential complementary source of these fatty acids. Our Perspective article focuses on the nutritional attributes of marine gammarids, including their naturally high levels of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), and considers their biological traits that support aquaculture practicality. We also examine the potential of marine gammarids for circular bioeconomy applications through trophic upgrading of low-value side streams. While evidence from feeding trials is limited, preliminary data suggest marine gammarids may maintain their high EPA and DHA content even when fed on low-quality diets. Critical research priorities include developing scalable production systems, optimising feed formulations, evaluating performance across key aquaculture species, and assessing ecological and operational feasibility. This Perspective also highlights the potential of marine gammarids to contribute to a diversified and resilient aquafeed portfolio. Although they are unlikely to replace fish meal or fish oil entirely, marine gammarids may serve as a strategic complementary ingredient.

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Morphological and genetic insights involved in latex synthesis and laticiferous vessel formation in Hevea spp. seedlings grown in vitro using plant growth regulators - Ana Claudia L. da Silva; Josiane Celerino de Carvalho; Thais Andrade Germano; Pedro Paulo dos Santos; Andreia Varmes Fernandes; José Hélio da Costa; Maria Izabel F. Guedes; Rivadalve Coelho Gonçalves; Wagner L. Araújo; Wagner C. Otoni; Adriano Nunes-Nesi; José Francisco de Carvalho Gonçalves (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Foraminiferal palaeoecology of the Aptian/Albian deposits of the Romualdo Formation (Araripe Basin) in northeastern of Brazil - Rilda C. Araripe; David H. D. Oliveira; Marta C. Viviers; Renata Moura De Mello; Anne C. M. Brandão; Bruno Fernandes; Rizoaldo Barbosa; Anny R. de A. Carvalho; Jefferson Santos; Maria Emília T. R. Tomé; Flávia A. Pedrosa Lemos; Ludmila A. C. Do Prado; et al. (Palaeobiodiversity and Palaeoenvironments, 2025)

In-situ electrogeneration of H2O2 and hydroxyl radical applied for venlafaxine degradation: A novel strategy using FeSe2-modified carbon gas diffusion electrode - Fausto E. Bimbi Júnior; Oswaldo C. Junior; Robson S. Souto; João Pedro P. Encide; Micael M. Baruch; Maria C.V. Felipe; Larissa Fernandes; Isabela F. Araujo; Carlos H.M. Fernandes; Igor G.S. Oliveira; Kathia M. Honorio; Renata Colombo; et al. (Chemical Engineering Journal, 2025)

Organic matter sources and productivity variations in the southeastern Bay of Bengal in the past 54,000 years - Maria C. Fernandes; Tyson Sebastian; Sunil Vadakkepuliyambatta; Pratheeksha Nayak; Madhusudan G. Yadava; Palayil John Kurian (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Effects of soybean molasses on ruminal fermentation pattern, performance and meat quality of feedlot sheep - Sérgio A.G. Pereira-Junior; Juliana A. Torrecilhas; Rayanne V. Costa; Edivilson S. Castro Filho; Maria Carolina G. Arruda; João Pedro A. Bertoco; Andresa L. Feliciano; Julia L. Rodrigues; Rosemary L. Galati; Angélica C. dos Santos; Marcos R. Chiaratti; Ricardo P. Nociti; et al. (Small Ruminant Research, 2025)

Rice husk silica derived MICROSCAFS® for a green solar-driven photodegradation of minocycline in aqueous media - Francesca Langiano; Sofia Moreira Fernandes; Beatriz Trindade Barrocas; Anna Del Tedesco; Pietro Riello; Maria João Ferreira; Ana C. Marques; Massimo Sgarzi; Matteo Gigli; Claudia Crestini (Journal of Water Process Engineering, 2025)

Addressing the urgent climate and biodiversity crisis through strategic ecosystem restoration in Brazil - Luisa Fernanda Liévano-Latorre; Juliana M. de Almeida-Rocha; Alberto Akama; Hernani Alves Almeida; Ricardo Teixeira Gregório Andrade; Marcelo Rodrigues dos Anjos; Yasmine Antonini; Thaise de Oliveira Bahia; Flavia Rodrigues Barbosa; Reinaldo Imbrozio Barbosa; Claudia Franca Barros; Helena Godoy Bergallo; et al. (Biological Conservation, 2025)

Enteroaggregative Escherichia coli (EAEC) isolates obtained from non-diarrheic children carry virulence factor-encoding genes from Extraintestinal Pathogenic E. Coli (ExPEC) - Bruna M. Luiz; Maria C. Cergole-Novella; Stéfani T. A. Dantas; Daiany R. P. de Lira; Guilherme F. R. de Souza; Iranildo do A. Fernandes; Henrique Orsi; Guilherme Solveira; Vera L. M. Rall; Luís F. dos Santos; Rodrigo T. Hernandes (Brazilian Journal of Microbiology, 2024)

3D Models as a Source for Neuroanatomy Education: A Stepwise White Matter Dissection Using 3D Images and Photogrammetry Scans - André S. B. Oliveira; João Vitor A. Fernandes; Vera Louise F. A. Figueiredo; Luciano C. P. C. Leonel; Megan M. J. Bauman; Michael J. Link; Maria Peris-Celda (Brain Topography, 2024)

The ADnet Bayesian belief network for alder decline: Integrating empirical data and expert knowledge - Inês Gomes Marques; Cristina Vieites-Blanco; Patricia M. Rodríguez-González; Pedro Segurado; Marlene Marques; Maria J. Barrento; Maria R. Fernandes; Arthur Cupertino; Helena Almeida; Idoia Biurrun; Tamara Corcobado; Filipe Costa e Silva; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Acquisition of elemental sulfur by sulfur‐oxidising Sulfolobales - Maria C. Fernandes‐Martins; Carli Springer; Daniel R. Colman; Eric S. Boyd (Environmental Microbiology, 2024)
Elemental sulfur (S 8 0 )‐oxidising Sulfolobales (Archaea) dominate high‐temperature acidic hot springs (>80°C, pH 8 0 ‐oxidising members of the Sulfolobales reveal a patchy distribution of genes encoding sulfur oxygenase reductase (SOR), an S 8 0 disproportionating enzyme attributed to S 8 0 oxidation. Here, we report the S 8 0 ‐dependent growth of two Sulfolobales strains previously isolated from acidic hot springs in Yellowstone National Park, one of which associated with bulk S 8 0 during growth and one that did not. The genomes of each strain encoded different sulfur metabolism enzymes, with only one encoding SOR. Dialysis membrane experiments showed that direct contact is not required for S 8 0 oxidation in the SOR‐encoding strain. This is attributed to the generation of hydrogen sulfide (H 2 S) from S 8 0 disproportionation that can diffuse out of the cell to solubilise bulk S 8 0 to form soluble polysulfides (S x 2− ) and/or S 8 0 nanoparticles that readily diffuse across dialysis membranes. The Sulfolobales strain lacking SOR required direct contact to oxidise S 8 0 , which could be overcome by the addition of H 2 S. High concentrations of S 8 0 inhibited the growth of both strains. These results implicate alternative strategies to acquire and metabolise sulfur in Sulfolobales and have implications for their distribution and ecology in their hot spring habitats.

Metaflumizone susceptibility baseline, reproduction, locomotion, and respiration responses on the Hypothenemus hampei - Caio S. Soares; Antônio G. de O. Nascimento; Natan S. Rocha; Ryan F.S. Silva; Daniel C. Nogueira; Jairo Tronto; Maria E.de S. Fernandes; Flávio L. Fernandes (Crop Protection, 2024)

Tropical forest succession increases tree taxonomic and functional richness but decreases evenness - Masha T. van der Sande; Lourens Poorter; Géraldine Derroire; Mario Marcos do Espirito Santo; Madelon Lohbeck; Sandra C. Müller; Radika Bhaskar; Michiel van Breugel; Juan Manuel Dupuy‐Rada; Sandra M. Durán; Catarina C. Jakovac; Horacio Paz; et al. (Global Ecology and Biogeography, 2024)
Aim Successional changes in functional diversity provide insights into community assembly by indicating how species are filtered into local communities based on their traits. Here, we assess successional changes in taxonomic and functional richness, evenness and redundancy along gradients of climate, soil pH and forest cover. Location Neotropics. Time period Last 0–100 years. Major taxa studied Trees. Methods We used 22 forest chronosequence studies and 676 plots across the Neotropics to analyse successional changes in Hill's taxonomic and functional diversity of trees, and how these successional changes vary with continental‐scale gradients in precipitation, soil pH and surrounding forest cover. Results Taxonomic and functional richness and functional redundancy increased, while taxonomic and functional evenness decreased over time. Functional richness and evenness changed strongly when not accounting for taxonomic richness, but changed more weakly after statistically accounting for taxonomic richness, indicating that changes in functional diversity are largely driven by taxonomic richness. Nevertheless, the successional increases in functional richness when correcting for taxonomic richness may indicate that environmental heterogeneity and limiting similarity increase during succession. The taxonomically‐independent successional decreases in functional evenness may indicate that stronger filtering and competition select for dominant species with similar trait values, while many rare species and traits are added to the community. Such filtering and competition may also lead to increased functional redundancy. The changes in taxonomically‐independent functional diversity varied with resource availability and were stronger in harsh, resource‐poor environments, but weak in benign, productive environments. Hence, in resource‐poor environments, environmental filtering and facilitation are important, whereas in productive environments, weaker abiotic filtering allows for high initial functional diversity and weak successional changes. Main conclusion We found that taxonomic and functional richness and functional redundancy increased and taxonomic and functional evenness decreased during succession, mainly caused by the increasing number of rare species and traits due to the arrival of new species and due to changing (a)biotic filters.

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Influence of structural Fe content in clay minerals on selenite redox reactions: Kinetics and structural transformations - Yanting Qian; Andreas C. Scheinost; Sylvain Grangeon; Alwina Hoving; Sergey V. Churakov; Maria Marques Fernandes (Geochimica et Cosmochimica Acta, 2024)

Evidence of plastics contamination and sewage-derived residues in a Brazilian Hope Spot for conservation of marine biodiversity - Cagarras Islands and surrounding waters - Raquel A.F. Neves; Nathália Rodrigues; Guilherme de Luca; Maria Alene A. Oliveira; Thuany F. Carvalho; Nicole S. Santos; Maria Eduarda S. Adelino; Luiza Belli Caldas; Agatha Miralha; Clarissa Naveira; Antonio J.S. Rodrigues; Igor C. Miyahira; et al. (Marine Pollution Bulletin, 2024)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Production of Oligosaccharides from Pine Nut Shells by Autohydrolysis - Ivone Torrado; Ana Dionísio; Maria C. Fernandes; Luísa Bivar Roseiro; Florbela Carvalheiro; Helena Pereira; Luís C. Duarte (BioEnergy Research, 2023)
Pinus pinea nuts are commercial relevant Mediterranean edible forest nuts, with an increasing production and market value, whose industrial processing yields a lignocellulosic by-product, the pine nut shells, currently only used for combustion. Little research has been done on pine nut shells that could support a value-added application for this residue. This work studies for the first time the production of oligosaccharides by autohydrosis, and aims at an integrated upgrade within the biorefinery framework. Autohydrolysis was explored in the temperature range between 150 and 230 °C (corresponding to severity factors 2.13–4.63). Oligosaccharides, mainly xylo-oligosaccharides (95% of the total), were the key soluble products, reaching 28.7 g/100 g of xylan of the feedstock at the optimal conditions (log R 0 4.01). Other products were monosaccharides and phenolic compounds that reached 7.8 and 4.7 g/L, respectively, under the most severe conditions. The stability of the oligosaccharides at different temperatures (room, 37 °C and 100 °C) and pH (between 1 and 11) grant them significant market potential in the food and pharma sectors. The pre-treated pine nut shells by autohydrolysis presented an improved, although low, enzymatic digestibility (14%), and an improved high-heating value, therefore advising their further valorization by thermochemical pathways.

How natural and anthropogenic factors should drive microplastic behavior and fate: The scenario of Brazilian urban freshwater - Fernando F. Sodré; Imisi M. Arowojolu; Maria C. Canela; Rodrigo S. Ferreira; Andreia N. Fernandes; Cassiana C. Montagner; Cristiane Vidal; Mariana A. Dias; Gilberto Abate; Leticia C. da Silva; Marco T. Grassi; Crislaine Bertoldi; et al. (Chemosphere, 2023)

In situ extraction/encapsulation of olive leaves antioxidants in zein for improved oxidative stability of edible oils - Amarilis Santos de Carvalho; Anielle de Oliveira; Thaysa Fernandes Moya Moreira; Luis Gustavo Médice Arabel Costa; Gabrielle Donato Marcatto; Andre da Silva Castilhos de Melo; Odinei Hess Gonçalves; Maria Inês Dias; Ricardo C. Calhelha; Lillian Barros; Patricia Valderrama; Lucio Cardozo Filho; et al. (Food Research International, 2023)

Low-cost materials for swine wastewater treatment using adsorption and Fenton’s process - Eva Domingues; João Lincho; Maria J. Fernandes; João Gomes; Rui C. Martins (Environmental Science and Pollution Research, 2023)
Untreated swine wastewater (SW) discharge leads to serious consequences such as water quality decreasing related to eutrophication and proliferation of harmful algae containing cyanotoxins, which can cause acute intoxication in humans. The use of untreated pig farming effluent as fertilizer can lead to the accumulation of polluting compounds. Biological treatments can degrade organic matter but have the disadvantage of requiring large areas and high retention times and demonstrating low efficiencies in the degradation of refractory compounds such as pharmaceutical compounds. In this ambit, the performance of four low-cost materials was evaluated for treatment of a swine wastewater using physical–chemical processes such as adsorption and Fenton’s process. The tested materials are two natural resources, red volcanic rock from Canary (RVR) Islands and black volcanic rock (BVR) from Azores, and two industry residues, red mud (RM) and iron filings (IF). Among the tested materials, only IFs are catalytically active for Fenton’s peroxidation. Still, RVR, BVR, and RM were efficient adsorbents removing up to 67% of COD. The combination between adsorption followed by Fenton’s process using IF as catalyst showed interesting results. When RM is applied as adsorbent in the diluted effluent, it was able to remove 67% and 90% of COD for adsorption and adsorption followed by IF Fenton, respectively. At those conditions, the resultant treated effluent accomplishes the requirements for direct discharge in the natural water courses as well as the parameters for water reusing.

Identification of Clinical Trichosporon asteroides Strains by MALDI-TOF Mass Spectrometry: Evaluation of the Bruker Daltonics Commercial System and an In-House Developed Library - Elaine Cristina Francisco; Mexx Ebbing; Arnaldo Lopes Colombo; Ferry Hagen; Guilherme M. Chaves; Ana Verena A. Mendes; Marcio de Oliveira Silva; Maria Goreth de Andrade Barberino; Rejane Pereira Neves; Monica Borges Botura; Rosane C. Hahn; João Nóbrega de Almeida Junior; et al. (Mycopathologia, 2023)

TRPV1 inactivation alters core body temperature and serum corticosterone levels: Impacts on clock genes expression in the liver and adrenal glands - Nayara AC. Horta; Paola Fernandes; Thais SR. Cardoso; Frederico SM. Machado; Lucas R. Drummond; Cândido C. Coimbra; Samuel P. Wanner; Ana Maria L Castrucci; Maristela O. Poletini (Journal of Thermal Biology, 2023)

Relationships between fluid mixing, biodiversity, and chemosynthetic primary productivity in Yellowstone hot springs - Maria C. Fernandes‐Martins; Daniel R. Colman; Eric S. Boyd (Environmental Microbiology, 2023)
The factors that influence biodiversity and productivity of hydrothermal ecosystems are not well understood. Here we investigate the relationship between fluid mixing, biodiversity, and chemosynthetic primary productivity in three co‐localized hot springs (RSW, RSN, and RSE) in Yellowstone National Park that have different geochemistry. All three springs are sourced by reduced hydrothermal fluid, but RSE and RSN receive input of vapour phase gas and oxidized groundwaters, with input of both being substantially higher in RSN. Metagenomic sequencing revealed that communities in RSN were more biodiverse than those of RSE and RSW in all dimensions evaluated. Microcosm activity assays indicate that rates of dissolved inorganic carbon (DIC) uptake were also higher in RSN than in RSE and RSW. Together, these results suggest that increased mixing of reduced volcanic fluid with oxidized fluids generates additional niche space capable of supporting increasingly biodiverse communities that are more productive. These results provide insight into the factors that generate and maintain chemosynthetic biodiversity in hydrothermal systems and that influence the distribution, abundance, and diversity of microbial life in communities supported by chemosynthesis. These factors may also extend to other ecosystems not supported by photosynthesis, including the vast subterranean biosphere and biospheres beneath ice sheets and glaciers.

Antimicrobial and anti-biofilm activity of silver nanoparticles biosynthesized with Cystoseira algae extracts - Mário Fernandes; Noelia González-Ballesteros; André da Costa; Raúl Machado; Andreia C. Gomes; Maria Carmen Rodríguez-Argüelles (JBIC Journal of Biological Inorganic Chemistry, 2023)
Antimicrobial resistance is an ever-growing global concern to public health with no clear or immediate solution. Silver nanoparticles (AgNPs) have long been proposed as efficient agents to fight the growing number of antibiotic-resistant strains. However, the synthesis of these particles is often linked to high costs and the use of toxic, hazardous chemicals, with environmental and health impact. In this study, we successfully produced AgNPs by green synthesis with the aid of the extract of two brown algae— Cystoseira baccata (CB) and Cystoseira tamariscifolia (CT)—and characterized their physico-chemical properties. The NPs produced in both cases (Ag@CB and Ag@CT) present similar sizes, with mean diameters of around 22 nm. The antioxidant activity of the extracts and the NPs was evaluated, with the extracts showing important antioxidant activity. The bacteriostatic and bactericidal properties of both Ag@CB and Ag@CT were tested and compared with gold NPs produced in the same algae extracts as previously reported. AgNPs demonstrated the strongest bacteriostatic and bactericidal properties, at concentrations as low as 2.16 µg/mL against Pseudomonas aeruginosa and Escherichia coli . Finally, the capacity of these samples to prevent the formation of biofilms characteristic of infections with a poorer outcome was assessed, obtaining similar results. This work points towards an alternative for the treatment of bacterial infections, even biofilm-inducing, with the possibility of minimizing the risk of drug resistance, albeit the necessary caution implied using metallic NPs. Graphical abstract

Quantification of SARS-CoV-2 in wastewater samples from hospitals treating COVID-19 patients during the first wave of the pandemic in Brazil - Juliana Calábria de Araújo; Camila L. Madeira; Thiago Bressani; Cíntia Leal; Deborah Leroy; Elayne C. Machado; Luyara A. Fernandes; Maria Fernanda Espinosa; Gabriel Tadeu O. Freitas; Thiago Leão; Vera Tainá Mota; Alyne Duarte Pereira; et al. (Science of The Total Environment, 2023)

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Variants in GCNA, X-linked germ-cell genome integrity gene, identified in men with primary spermatogenic failure - Jimmaline J. Hardy; Margot J. Wyrwoll; William Mcfadden; Agnieszka Malcher; Nadja Rotte; Nijole C. Pollock; Sarah Munyoki; Maria V. Veroli; Brendan J. Houston; Miguel J. Xavier; Laura Kasak; Margus Punab; et al. (Human Genetics, 2021)

Photocatalytic degradation of acetaminophen and caffeine using magnetite–hematite combined nanoparticles: kinetics and mechanisms - Tiago A. Fernandes; Sofia G. Mendo; Liliana P. Ferreira; Nuno R. Neng; M. Conceição Oliveira; Adrià Gil; Maria Deus Carvalho; Olinda C. Monteiro; José M. F. Nogueira; Maria José Calhorda (Environmental Science and Pollution Research, 2021)

Evaluation of Cerebellar Function and Integrity of Adult Rats After Long-Term Exposure to Aluminum at Equivalent Urban Region Consumption Concentrations - Rafael Monteiro Fernandes; Priscila Cunha Nascimento; Maria Karolina Martins; Walessa Alana Bragança Aragão; Luis Felipe Sarmiento Rivera; Leonardo Oliveira Bittencourt; Sabrina C. Cartágenes; Maria Elena Crespo-Lopez; Cristiane do Socorro Ferraz Maia; Rafael Rodrigues Lima (Biological Trace Element Research, 2021)

Chemical composition and larvicidal activity of the essential oil from the leaves of Onychopetalum periquino (Rusby) D.M. Johnson & N.A. Murray - Bruna R. de Lima; Felipe M. A. da Silva; Elzalina R. Soares; Richardson A. de Almeida; Jessica B. Maciel; Carromberth C. Fernandes; André C. de Oliveira; Wanderli P. Tadei; Hector H. F. Koolen; Afonso D. L. de Souza; Maria L. B. Pinheiro (Natural Product Research, 2021)

Diversity of tomato-infecting begomoviruses and spatiotemporal dynamics of an endemic viral species of the Brazilian Atlantic rain forest biome - Macária F. Duarte; Maria E. N. Fonseca; Hélcio Costa; Niday A. N. Fernandes; Ailton Reis; Leonardo S. Boiteux; Rita C. Pereira-Carvalho (Virus Genes, 2021)

Lake level oscillations recorded in Buracica Stage (Barremian, Early Cretaceous) of Recôncavo Basin, Bahia State (N.E. Brazil) - Jorge C. Della Fávera; Hemani A. Fernandes Chaves; Marco André Malmann Medeiros; Cícera Pereira de Meneses; Maria Edilmeire A. Tavares; Maria Eugenia González; Maria Luciete D. Pinheiro; Orlando Cristiano da Silva; Maria Virginia Alves Martins (Journal of Sedimentary Environments, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Proteomic and phosphoproteomic analyses reveal several events involved in the early stages of bovine herpesvirus 1 infection - Marcos J. Magalhães-Junior; Maria Cristina Baracat-Pereira; Lorena K. J. Pereira; Camilo E. Vital; Marcus R. Santos; Pricila S. Cunha; Kenner M. Fernandes; Gustavo C. Bressan; Juliana L. R. Fietto; Abelardo Silva-Júnior; Márcia R. Almeida (Archives of Virology, 2020)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Distillery Residues from Cistus ladanifer (Rockrose) as Feedstock for the Production of Added-Value Phenolic Compounds and Hemicellulosic Oligosaccharides - Júnia Alves-Ferreira; Luís C. Duarte; Ana Lourenço; Luísa B. Roseiro; Maria C. Fernandes; Helena Pereira; Florbela Carvalheiro (BioEnergy Research, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

The Inventory of Geological Heritage of the State of São Paulo, Brazil: Methodological Basis, Results and Perspectives - Maria da Glória Motta Garcia; José Brilha; Flávia Fernanda de Lima; Jean Carlos Vargas; Annabel Pérez-Aguilar; Adriana Alves; Ginaldo Ademar da Cruz Campanha; Wânia Duleba; Frederico Meira Faleiros; Luiz Alberto Fernandes; Marisa de Souto Matos Fierz; Maria Judite Garcia; et al. (Geoheritage, 2018)

Standardization and Prevalence of the Booster Phenomenon: Evaluation Using a Two-Step Skin Test with 43 kDa Glycoprotein in Individuals from an Endemic Region of Paracoccidioidomycosis - Ana Paula C. Marques; Sandra Maria V. L. Oliveira; Grazielli R. Rezende; Dayane A. Melo; Sonia M. Fernandes-Fitts; Elenir Rose J. C. Pontes; Maria da Glória Bonecini-Almeida; Zoilo P. Camargo; Rinaldo P. Mendes; Anamaria M. M. Paniago (Mycopathologia, 2017)

Tropical specialist vs. climate generalist: Diversification and demographic history of sister species of Carlia skinks from northwestern Australia - Ana C. Afonso Silva; Jason G. Bragg; Sally Potter; Carlos Fernandes; Maria Manuela Coelho; Craig Moritz (Molecular Ecology, 2017)
Species endemic to the tropical regions are expected to be vulnerable to future climate change due in part to their relatively narrow climatic niches. In addition, these species are more likely to have responded strongly to past climatic change, and this can be explored through phylogeographic analyses. To test the hypothesis that tropical specialists are more sensitive to climate change than climate generalists, we generated and analyse sequence data from mt DNA and ~2500 exons to compare scales of historical persistence and population fluctuation in two sister species of Australian rainbow skinks: the tropical specialist Carlia johnstonei and the climate generalist C. triacantha . We expect the tropical specialist species to have deeper and finer‐scale phylogeographic structure and stronger demographic fluctuations relative to the closely related climate generalist species, which should have had more stable populations through periods of harsh climate in the late Quaternary. Within C. johnstonei , we find that some populations from the northern Kimberley islands are highly divergent from mainland populations. In C. triacantha , one major clade occurs across the deserts and into the mesic Top End, and another occurs primarily in the Kimberley with scattered records eastwards. Where their ranges overlap in the Kimberley, both mitochondrial DNA and nuclear DNA suggest stronger phylogeographic structure and range expansion within the tropical specialist, whereas the climate generalist has minimal structuring and no evidence of recent past range expansion. These results are consistent with the hypothesis that tropical specialists are more sensitive to past climatic change.

Cytokines profile and its correlation with endothelial damage and oxidative stress in patients with type 1 diabetes mellitus and nephropathy - Rodrigo M. C. Pestana; Caroline P. Domingueti; Rita C. F. Duarte; Rodrigo B. Fóscolo; Janice S. Reis; Ana Maria S. Rodrigues; Laís B. Martins; Lirlândia P. Sousa; Daniela P. Lage; Cláudia N. Ferreira; Adaliene V. M. Ferreira; Ana P. Fernandes; et al. (Immunologic Research, 2016)

“Cytochrome c oxidase I DNA sequence of Camponotus ants with different nesting strategies is a tool for distinguishing between morphologically similar species” - Manuela O. F. Ramalho; Rodrigo M. Santos; Tae T. Fernandes; Maria Santina C. Morini; Odair C. Bueno (Genetica, 2016)

Enhanced textile dye decolorization by marine-derived basidiomycete Peniophora sp. CBMAI 1063 using integrated statistical design - Rafaella C. Bonugli-Santos; Gabriela A. L. Vieira; Catherine Collins; Thaís Cristina C. Fernandes; Maria Aparecida Marin-Morales; Patrick Murray; Lara D. Sette (Environmental Science and Pollution Research, 2016)

Genetic background of novel sequence types of CTX-M-8- and CTX-M-15-producing Escherichia coli and Klebsiella pneumoniae from public wastewater treatment plants in São Paulo, Brazil - Milena Dropa; Nilton Lincopan; Livia C. Balsalobre; Danielle E. Oliveira; Rodrigo A. Moura; Miriam Rodriguez Fernandes; Quézia Moura da Silva; Glavur R. Matté; Maria I. Z. Sato; Maria H. Matté (Environmental Science and Pollution Research, 2016)

Role of sediment size in the distribution and abundance of metals in a tropical (Sharavati) estuary, west coast of India - Maria C. Fernandes; G. N. Nayak (Arabian Journal of Geosciences, 2016)

Evaluation of flavonols and derivatives as human cathepsin B inhibitor - Suelem D. Ramalho; Lorena R. F. de Sousa; Marcela C. M. Burger; Maria Inês S. Lima; M. Fátima das G. F. da Silva; João B. Fernandes; Paulo C. Vieira (Natural Product Research, 2015)

Polymorphism in apoptotic BAX (-248G>A) gene but not in anti-apoptotic BCL2 (-938C>A) gene and its protein and mRNA expression are associated with cervical intraepithelial neoplasia - Ana Teresa G. Fernandes; Natália P. Rocha; Elena Vendrame; Fabio Russomano; Beatriz J. Grinsztejn; Ruth K. Friedman; Amanda C. Pinto; Evandro M. Klumb; Elyzabeth Avvad; Jacyara Macedo; Otoniel Martínez-Maza; Maria da Gloria Bonecini-Almeida (Apoptosis, 2015)

Larvicidal, molluscicidal and nematicidal activities of essential oils and compounds from Foeniculum vulgare - Rose Marie O. F. Sousa; José S. Rosa; Cláudia A. Silva; Maria Teresa M. Almeida; M. Teresa Novo; Ana C. Cunha; Manuel Fernandes-Ferreira (Journal of Pest Science, 2015)

3-Indol carboxaldehyde, an imidazole synthesized from naphthoquinone β-lapachone downregulates Candida albicans biofilm - José Alexandre da Rocha Curvelo; Anna Lea Silva Barreto; Camila A. dos Anjos; Rafaela S. Santana; Ariadne Nunes Alonso; Maria Teresa Vilela Romanos; Kelly C. G. de Moura; Paula Fernandes Carneiro; Maristela Barbosa Portela; Maria do Carmo F. R. Pinto; Rosangela Maria de Araújo Soares (Medicinal Chemistry Research, 2015)

Phthaloyl amino acids as anti-inflammatory and immunomodulatory prototypes - Ana Cristina Lima Leite; Fábio Fernandes Barbosa; Marcos Veríssimo de Oliveira Cardoso; Diogo R. M. Moreira; Lucas Cunha D. Coêlho; Elany Barbosa da Silva; Gevanio Bezerra de Oliveira Filho; Valdênia Maria Oliveira de Souza; Valéria Rêgo A. Pereira; Luiza de C. Reis; Paulo Michel Pinheiro Ferreira; Claudia Pessoa; et al. (Medicinal Chemistry Research, 2014)

Evaluation of Paracoccidioides brasiliensis Infection by gp 43 Intradermal Test in Rural Settlements in Central-West Brazil - Ana Paula da C. Marques; Sandra Maria V. L. Oliveira; Grazielli R. Rezende; Dayane A. Melo; Sonia M. Fernandes-Fitts; Elenir Rose J. C. Pontes; Maria da Glória Bonecini-Almeida; Zoilo P. Camargo; Anamaria M. M. Paniago (Mycopathologia, 2013)

HFE, MTHFR, and FGFR4 genes polymorphisms and breast cancer in Brazilian women - Anna P. Batschauer; Nathalia G. Cruz; Vanessa C. Oliveira; Fernanda F. Coelho; Izabela R. Santos; Michelle T. Alves; Ana P. Fernandes; Maria G. Carvalho; Karina B. Gomes (Molecular and Cellular Biochemistry, 2011)

Mutations in methylenetetrahydrofolate reductase and in cysthationine beta synthase: is there a link to homocysteine levels in peripheral arterial disease? - Maria E. R. C. Santos; Francisco das C. L. e Silva; Karina B. Gomes; Ana Paula M. Fernandes; Fernanda R. Freitas; Mayara C. Faria; Ana Paula L. Mota; Maria G. Carvalho (Molecular Biology Reports, 2011)

Vasodilator effects of Diocleinae lectins from the Canavalia genus - Ana Maria Sampaio Assreuy; Sabrina Rodrigues Fontenele; Alana de Freitas Pires; Débora Costa Fernandes; Natália Velloso Fontenelle C. Rodrigues; Eduardo Henrique Salviano Bezerra; Tales Rocha Moura; Kyria Santiago do Nascimento; Benildo Sousa Cavada (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Insights into the pathobiology of Paracoccidioides brasiliensis from transcriptome analysis—advances and perspectives - Simoneide S. Silva; Hugo C. Paes; Célia M. A. Soares; Larissa Fernandes; Maria Sueli S. Felipe (Mycopathologia, 2008)

The effects of peroxovanadate and peroxovanadyl on glucose metabolism in vivo and identification of signal transduction proteins involved in the mechanism of action in isolated soleus muscle - Ricado Key Yamazaki; Sandro M. Hirabara; Osvaldo Tchaikovski; Maria Cecília Pascoal Lopes; Claudia Nogata; Júlia Aikawa; Everson A. Nunes; Ricardo A. Tanhoffer; Maurício D. Lissa; L. C. Fernandes (Molecular and Cellular Biochemistry, 2005)

Hepatoprotective activity of polyhydroxylated 2-styrylchromones against tert-butylhydroperoxide induced toxicity in freshly isolated rat hepatocytes - Eduarda Fernandes; Márcia Carvalho; Félix Carvalho; Artur M. S. Silva; Clementina M. M. Santos; Diana C. G. A. Pinto; José A. S. Cavaleiro; Maria de Lourdes Bastos (Archives of Toxicology, 2003)